Impurity Substitution Enhances Thermoelectric Figure of Merit in Zigzag Graphene Nanoribbons - Saeideh Ramezani Akbarabadi; Mojtaba Madadi Asl (Advances in Condensed Matter Physics)
The thermoelectric properties of zigzag graphene nanoribbons (ZGNRs) are sensitive to chemical modification. In this study, we employed density functional theory (DFT) combined with the nonequilibrium green’s function (NEGF) formalism to investigate the thermoelectric properties of a ZGNR system by impurity substitution of single and double nitrogen (N) atoms into the edge of the nanoribbon. N-doping changes the electronic transmission probability near the Fermi energy and suppresses the phononic transmission. This results in a modified electrical conductance, thermal conductance, and thermopower. Ultimately, simultaneous increase of the thermopower and suppression of the electron and phonon contributions to the thermal conductance leads to the significant enhancement of the figure of merit in the perturbed (i.e., doped) system compared to the unperturbed (i.e., nondoped) system. Increasing the number of dopants not only changes the nature of transport and the sign of thermopower but also further suppresses the electron and phonon contributions to the thermal conductance, resulting in an enhanced thermoelectric figure of merit. Our results may be relevant for the development of ZGNR devices with enhanced thermoelectric efficiency.